PENGARUH E-SERVICE QUALITY TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING DI E-COMMERCE SHOPEE (STUDI KASUS PADA GEN-Z KOTA PALU) - Prabawanti, Kd. Jessika; Bachri, Syamsul; Ponirin, Ponirin; Asriadi, Asriadi (Journal of Economic, Bussines and Accounting (COSTING), 2024)
A primary factor affecting the success of an e-commerce platform is the quality of its electronic services, which is crucial in fostering customer satisfaction and loyalty. This research aims to examine the impact of e-service quality on customer loyalty, with customer satisfaction serving as an intervening variable, specifically targeting Generation Z users of Shopee in Palu. The study employs a quantitative approach, focusing on Generation Z Shopee users in Palu as the population. The sample was selected through non-probability sampling, specifically judgmental sampling, and consists of 110 respondents. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Square (PLS), facilitated by Smart PLS 4.0 software. Findings reveal that e-service quality has a positive and significant impact on both customer satisfaction and loyalty, customer satisfaction significantly enhances customer loyalty, and customer satisfaction successfully mediates the link between e-service quality and customer loyalty in a positive and significant way. This underscores the need to improve e-service quality to boost customer satisfaction and loyalty, suggesting that e-commerce platforms like Shopee should prioritize digital service optimization to enhance competitiveness and retain loyal customers.